STANDRDS FOR VARIATION RANGE OF RR-INTERVALS AT REST AND IN ORTHOSTASIS IN TRAINING OF RACING SKIERS WITH DIFFERENT TYPES OF REGULATION - Shlyk, N.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify standards for the variation range of RR-intervals at rest and in orthostasis in training of racing skiers with different types of regulation Methods and structure of the study. During the study, we conducted 559 dynamic HRV tests at rest and in orthostasis at different stages of the training cycle. Subject to the study were 34 racing skiers aged 17-22 years, having the sports qualifications of I adult category, CMS, and MS. The subjects were tested in the morning after the previous training day before the first training using the Varikard 2.51 hardware-software complex and Varikard MP program (Ryazan, Russia). The predominant type of autonomic regulation was defined by the classification proposed by N.I. Shlyk. Prior to each HRV test, the racing skiers were interviewed about the physical loads performed on the previous training day, their load tolerance, quality of sleep, well-being, and participation in competitions. Results and conclusion. The study found that the predominant type of regulation at rest in each athlete defines the bounds of the MxDMn range, divisions of the autonomic nervous system, and level of the body’s functioning as a whole. Therefore, racing skiers with different MxDMn values and vegetative balances should be subjected to different training loads, which would help timely prevent overstrain and overtraining. The lack of clarity over the bounds of the optimal MxDMn range, or disregard of this indicator in the HRV analysis of racing skiers cannot provide researchers with true information on the level of tolerance to physical loads.